2012
DOI: 10.1142/s0217979212500737
|View full text |Cite
|
Sign up to set email alerts
|

MÖSSBAUER AND HIGH-TEMPERATURE MAGNETIC PROPERTIES OF DIFFERENT SIZE Fe3O4 NANOSTRUCTURE

Abstract: We examine size-dependent structural and magnetic properties of fine size controlled iron oxide nanoparticles in the 4–17 nm range confirmed by XRD. Through Mössbauer spectra, we found that the ratio of Fe 3+/ Fe +2.5 and the Fe vacancies on the B sites can be modified by varying the particle size. Coating Fe 3 O 4 nanoparticles with SiO 2 effectively eliminates magnetic interparticle interactions so that the Curie temperature (Tc) can be well fitted by an expression for noninteracting randomly oriented single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…At present, it becomes more clear that, at high temperatures, the temperature at which the saturation magnetization reaches zero (Curie temperature (T C )), when the transition from the ferromagnetic (or ferrimagnetic) state to the paramagnetic state occurs, depends on the size of nanoparticles: the Curie temperature of the nanoparticle system decreases, as the diameter of nanoparticles decreases, a fact proved both experimentally and theoretically [44][45][46][47][48][49]. It was shown that the Curie temperature can be expressed in relation to diameter of nanoparticle (D) by finite-size scaling law [50] (in agreement with Monte Carlo (MC) simulation),…”
Section: The Variation Of the Nanoparticle Saturation Magnetization Wmentioning
confidence: 98%
“…At present, it becomes more clear that, at high temperatures, the temperature at which the saturation magnetization reaches zero (Curie temperature (T C )), when the transition from the ferromagnetic (or ferrimagnetic) state to the paramagnetic state occurs, depends on the size of nanoparticles: the Curie temperature of the nanoparticle system decreases, as the diameter of nanoparticles decreases, a fact proved both experimentally and theoretically [44][45][46][47][48][49]. It was shown that the Curie temperature can be expressed in relation to diameter of nanoparticle (D) by finite-size scaling law [50] (in agreement with Monte Carlo (MC) simulation),…”
Section: The Variation Of the Nanoparticle Saturation Magnetization Wmentioning
confidence: 98%